Interpersonal Relations and Task Performance - Timinepere Ogele Court; Godknows Nein (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The study draws on the social network theory to examine the influence of interpersonal relations on the task performance at the individual employee, team and divisional levels in the Nigerian Police Force. Design/methodology/approach: The study adopted a cross sectional survey design and a sample of 556 police men was selected through the application of multi-stage sampling procedures. The data collection instrument was designed in line with the 5-point Likert scale while the instrument was validated through content validity approach and the reliability of the instrument is determined using the test-retest method. Findings: Data were collected through the self-report of the policemen while analysis was carried out using descriptive statistics, run mean test and Chi-square test and the results indicated that interpersonal relations influence employee, team and divisional task performance in the Nigerian Police Force. Practical implications: We recommended that instrumental ties and social communities in the fabric of the Nigerian Police Force should be promoted to further advance the critical roles of crime fighting and prevention with a view to reducing criminality in Nigeria. Originality/value: To the best of the authors' knowledge, this research is original and adds new value to the field by being the first of its kind. Paper type: Research paper